ANALISIS PENGARUH INFLASI, NILAI TUKAR, SUKU BUNGA, DAN JUMLAH UANG BEREDAR TERHADAP NILAI EKSPOR DI INDONESIA TAHUN 2020-2023 - Yefta Fikanur Febiana; Wulan Wahyu Ning Tias; Dina Farikhatul Amna; Rizquna Salsabila; Bintis Tianatud Diniati (Sekolah Tinggi Ilmu Ekonomi Bakti Bangsa, 2024)
This study analyzes the effect of inflation, exchange rates, interest rates, and money supply on the value of exports in Indonesia for 4 years 2020-2023. It aims to understand how these factors affect the value of exports. The method used is quantitative analysis with time series data obtained from BPS, BI, and the Ministry of Trade, including four dependent variables (inflation, exchange rates, interest rates, and money supply) and one independent variable (exports). The results show that inflation and money supply have a significant influence on exports. However, exchange rates and interest rates do not have a significant effect. Simultaneously, all independent variables significantly affect the value of exports. In conclusion, these factors have an important role in influencing the value of exports in Indonesia.